First annotated draft genomes of nonmarine ostracods (Ostracoda, Crustacea) with different reproductive modes. Issue 4 (16th February 2021) - Tran Van, Patrick; Anselmetti, Yoann; Bast, Jens; Dumas, Zoé; Galtier, Nicolas; Jaron, Kamil S; Martens, Koen; Parker, Darren J; Robinson-Rechavi, Marc; Schwander, Tanja; Simion, Paul; Schön, Isa
Abstract: Ostracods are one of the oldest crustacean groups with an excellent fossil record and high importance for phylogenetic analyses but genome resources for this class are still lacking. We have successfully assembled and annotated the first reference genomes for three species of nonmarine ostracods; two with obligate sexual reproduction ( Cyprideis torosa and Notodromas monacha ) and the putative ancient asexual Darwinula stevensoni . This kind of genomic research has so far been impeded by the small size of most ostracods and the absence of genetic resources such as linkage maps or BAC libraries that were available for other crustaceans. For genome assembly, we used an Illumina-based sequencing technology, resulting in assemblies of similar sizes for the three species (335–382 Mb) and with scaffold numbers and their N50 (19–56 kb) in the same orders of magnitude. Gene annotations were guided by transcriptome data from each species. The three assemblies are relatively complete with BUSCO scores of 92–96. The number of predicted genes (13, 771–17, 776) is in the same range as Branchiopoda genomes but lower than in most malacostracan genomes. These three reference genomes from nonmarine ostracods provide the urgently needed basis to further develop ostracods as models for evolutionary and ecological research.